GENEALOGY OF THE “PUBLIC GOOD” - LIBERALISM AND SOCIETY. Part 1 - Маркова, Илинида (E-Journal VFU, 2025)
The already present and potential weaknesses of human society have been constantly in the sight of wisdom throughout the ages. The escalation of negative characteristics in the twenty-first century stands in stark contrast to the ideals of previous eras. The text attempts to analyze the causes of the negatives, as the ancient belief that the problem can only be solved if it is seen is valid today.
Keywords: „Public good”; liberalism; conservatism; virtue